Large left oblique inguinal-scrotal hernia with bladder involvement in the hernial sac: diagnostics and surgical treatment - A. G. Ivanov; Yu. V. Khoron'ko (Вестник урологии)
Data from a patient's medical history with a sliding inguinal-scrotal hernia with bladder involvement in the hernia sac was studied. The data of general clinical and instrumental examination, intraoperative data and the results of surgical treatment are presented. A large sliding inguinal-scrotal hernia with the involvement of the bladder in the hernia sac has been eliminated. Prostate adenoma of considerable size is preserved. In the postoperative period, a decrease in the severity of urinary disorders. Moved from the scrotum, the bladder is fully expanded. However, it remains unclear the functionality of that area of he bladder which was located in the hernial sac.